83.8k views
4 votes
Prove that

x {}^(2) + y {}^(2) > xy


User Seanyboy
by
5.5k points

2 Answers

5 votes

Answer:

Explanation:

hello :

note : add for your statement : x>0 and y>0

look this solution :

Prove that x {}^(2) + y {}^(2) > xy ​-example-1
User Jagger
by
5.9k points
4 votes

Answer:

Proof in explanation.

Explanation:

I'm going to assume you mean "greater than or equal to".

We know
(x-y)^2 \ge 0.

We know this because any real number squared will result in a positive or zero result.

Let's expand the left hand side:


(x-y)(x-y) \ge 0

Distribute:


x(x-y)-y(x-y) \ge 0


x^2-xy-yx+y^2 \ge 0

Combine like terms:


x^2-2xy+y^2 \ge 0

Commutative property of addition:


x^2+y^2-2xy \ge 0

Add
2xy on both sides:


x^2+y^2 \ge 2xy

Now we wanted to show
x^2+y^2 \ge xy. Our right hand side almost appeared that way except the factor of 2 present there.

Let's go back to our inequality that we got:


x^2+y^2 \ge 2xy

Divide both sides by 2:


(x^2+y^2)/(2) \ge xy

Note: Half of a positive number is less than that positive number.


x^2+y^2 \ge (x^2+y^2)/(2) \ge xy

This inequality says we would like it to say in the end:


x^2+y^2 \ge xy

User Tlum
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.